Bioaugmentation with native Bacillus strains enhance nitrate and nitrite removal and reshape microbiomes in low-salinity shrimp cultures: Elucidating genetic mechanisms - Dámaris Adelaida Esquén Bayona; Delia Talledo Ancajima; Dorian Adriano Cadena; Luz Dominguez-Mendoza; Sebastian Leyva; Mia Mariana Somocurcio Zambrano; David Edilberto Saldarriaga Yacila; Pabulo Henrique Rampelotto; Frank Lino Guzman Escudero; Benoit Mathieu Diringer (PLoS ONE, 2026)
The intensification of shrimp farming contributes to the accumulation of toxic nitrogen compounds, which in turn affect productivity and complicates water quality management, especially under conditions of reduced salinity. This study evaluated the effects of 25% (CO, T2) and 50% (T1) water exchange, in combination with a bioaugmentation treatment using native Bacillus (T2), on nitrogen compound concentrations and bacterial community structure in Litopenaeus vannamei culture under reduced salinity conditions (4ppt). The results demonstrated that treatment with native Bacillus megaterium and Bacillus paralicheniformis (T2) leads to a significant reduction in nitrite and nitrate concentrations, reaching nearly 0 mg/L from day 4. In contrast, T1 and CO treatments showed markedly higher concentration, reaching up to 5 mg/mL and 160 mg/L, respectively. The full-length 16S rRNA gene used for the metataxonomic analysis revealed changes in bacterial composition towards species with nitrifying and probiotic potential, with native Bacillus strains detected exclusively in T2. In addition, a reduction in bacterial diversity was detected, and significant differences were observed between the bacterial communities of T2 and those of T1 and CO (p = 0.001, R 2 = 0,328). The shotgun analysis further revealed a higher abundance of enzymes related to nitrification and dissimilatory nitrate reduction to ammonium in T2 treatment. The results highlighted the active involvement of Gram positive – Bacillus and Gram-negative bacteria such as Shewanella and Psychrobacter , and suggesting heterotrophic nitrification and aerobic denitrification. Overall, native B. megaterium and B. paralicheniformis provided an effective bioaugmentation strategy for the managing nitrate and nitrite in low-salinity shrimp farming, providing an eco-friendly alternative that may enhance productivity and reduce the industry´s water footprint.